2012
DOI: 10.1063/1.4723648
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary effects on defect production and mechanical properties of irradiated nanocrystalline SiC

Abstract: Grain boundaries (GBs) are known to play an important role in determining the mechanical and functional properties of nanocrystalline materials. In this study, we used molecular dynamics simulations to investigate the effects of damaged GBs on the mechanical properties of SiC that is irradiated by 10 keV Si atoms. The results reveal that irradiation promotes GB sliding and reduces the ability of GBs to block dislocations, which improves the deformation ability of nanocrystalline SiC. However, irradiation cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…As a result, the shape of grains changed and the nano-columns became narrow under irradiation. The amorphization processes of our present simulations are in good agreement with these experimental observations, and consistent with the molecular dynamics (MD) simulations of irradiated nanocrystalline SiC by Niu et al 13 who found the same trend of damage accumulation processes in irradiation-induced amorphization. Cascade simulations in nanocrystalline SiC have showed that the number of defects produced in a cascade primarily depends on the volume fraction of GB and more defects are produced along the GB due to the lower threshold displacement energies 14 .…”
Section: Resultssupporting
confidence: 92%
“…As a result, the shape of grains changed and the nano-columns became narrow under irradiation. The amorphization processes of our present simulations are in good agreement with these experimental observations, and consistent with the molecular dynamics (MD) simulations of irradiated nanocrystalline SiC by Niu et al 13 who found the same trend of damage accumulation processes in irradiation-induced amorphization. Cascade simulations in nanocrystalline SiC have showed that the number of defects produced in a cascade primarily depends on the volume fraction of GB and more defects are produced along the GB due to the lower threshold displacement energies 14 .…”
Section: Resultssupporting
confidence: 92%
“…Previous researches have also found that grain boundary is an effective sink for atomic defects introduced by irradiation in zinc-blend SiC. [27][28][29] The defect density distribution along the radial direction is defined by the number of rings in a hollow cylinder with the same axis as the nanowires divided by its volume (inset in Fig. 3(d)).…”
Section: Resultsmentioning
confidence: 98%
“…However, nc‐SiC with grains sizes in the range 30–50 nm did not show significant differences with respect to single crystals under ion‐irradiation at RT . Also, even though in many materials GBs strongly interact with the displacement cascades, many studies indicate that there is no direct effect of the GBs on the primary defect production in SiC …”
Section: Discussionmentioning
confidence: 96%
“…54 Also, even though in many materials GBs strongly interact with the displacement cascades, 55 many studies indicate that there is no direct effect of the GBs on the primary defect production in SiC. [56][57][58] As discussed by Jiang et al, 49 disorder accumulation in a crystalline grain cannot be avoided unless the point defects produced during irradiation are completely recovered before the next displacement event in the crystallite. A rough estimation of the mean diffusion length (l D ), for Si and C interstitials and vacancies at 200°C can be calculated using the expression l D ¼ ffiffiffiffiffiffiffiffi 2Dt p , being D the diffusion coefficient for the desired point defect, and t the time between two consecutive displacement events.…”
Section: Discussionmentioning
confidence: 99%